1989
DOI: 10.1172/jci114353
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel cytokine and its gene (LD78) expressions in hematopoietic fresh tumor cells and cell lines.

Abstract: Thus, the protein may be involved in the neoplastic transformation of hematopoietic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Moreover, several secreted (cytokine) and cell surface-associated (receptor) factors serve as important clues for monitoring the activity and prognosis of patients with ATL/ATLL (Yasuda et al 1988;Yamada et al 1996;Mori and Prager 1998). We have also shown that ATL/ ATLL cells express the chemokine ligand 3 (Yamamura et al 1989). Subsequently, ATL/ATLL cells were found to be CCR4 + , which led to the development of anti-CCR4 monoclonal antibody (MoAb) therapy (KW-0761 or mogamulizumab) after discovering that about 90% of ATL/ATLL samples are positive for CCR4 (Ishida et al 2003).…”
Section: Introductionmentioning
confidence: 60%
“…Moreover, several secreted (cytokine) and cell surface-associated (receptor) factors serve as important clues for monitoring the activity and prognosis of patients with ATL/ATLL (Yasuda et al 1988;Yamada et al 1996;Mori and Prager 1998). We have also shown that ATL/ ATLL cells express the chemokine ligand 3 (Yamamura et al 1989). Subsequently, ATL/ATLL cells were found to be CCR4 + , which led to the development of anti-CCR4 monoclonal antibody (MoAb) therapy (KW-0761 or mogamulizumab) after discovering that about 90% of ATL/ATLL samples are positive for CCR4 (Ishida et al 2003).…”
Section: Introductionmentioning
confidence: 60%
“…Murine MIP-la has already been demonstrated to have inflammatory and chemokinetic properties (11,50). Recently, we found that high levels of LD78 gene transcripts are present in acute nonlymphotic as well as lymphotic leukemic cells; hence, LD78 is also probably involved in the neoplastic transformation of hematopoietic cells (51).…”
mentioning
confidence: 88%
“…Similarly, as mentioned above, SCI/MIP-lI mRNA is super-induced during endotoxin (lipopolysacharride, LPS) stimulation of murine macrophages (Davatelis et al, 1988), and is super-induced in human T-cell lines by phorbol esters (PMA) and/or PHA and cyclohexamide (Obaru et al, 1986;Yamamura et al, 1989;Blum et al, 1990). Interestingly, a basal level of SCI/MIP-lac mRNA is detected in unstimulated cultured murine macrophage Davatelis et al, 1988) and mast cell lines (Gordon et al, 1990, and M.P. unpublished results), whereas it is undetectable in unstimulated human monocyte (U937) and T-cell (Jurkat) lines although it can be induced by PHA and/or PMA (Obaru et al, 1986;Yamamura et al, 1989;Blum et al, 1990).…”
mentioning
confidence: 82%
“…Although it is unlikely that the SCI/MIP-la gene is itself directly involved in the cellular transformation process, nearby genetic lesions which activate proto-oncogenes or inactive suppressor genes may also coincidentally lead to aberrant SCI/MIP-la gene expression. The up-regulation of SCI/MIP-Ia gene expression has been detected in the peripheral blood of a number of ANLL and ALL patients (Yamamura et al, 1989) (Lord & Wright, 1980) and monocytes (Pojda et (Yamamura et al, 1989) and mast cells (Gordon et al, 1990 (Davatelis et al, 1988) and human (Forsdyke, 1985;Obaru et al, 1986;Zipfel et al, 1989) SCI/MIP-lI cDNAs revealed a number of conserved (TATTT) motifs in the 3' untranslated region of the mRNA which have been implicated in the modulation of mRNA stability of a number of other cytokine mRNAs (Caput et al, 1986;Shaw & Kamen, 1986). Similarly, as mentioned above, SCI/MIP-lI mRNA is super-induced during endotoxin (lipopolysacharride, LPS) stimulation of murine macrophages (Davatelis et al, 1988), and is super-induced in human T-cell lines by phorbol esters (PMA) and/or PHA and cyclohexamide (Obaru et al, 1986;Yamamura et al, 1989;Blum et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation